Exploring the characteristics of cancer-centred civil society organisations in Chile: A qualitative study - Antonia Roberts; Francisca Vezzani; Báltica Cabieses; Alexandra Obach; Carla Campaña; Manuel A. Espinoza (PLoS ONE, 2025)
Background In Chile, civil society organisations in health have been historically active in population health and specifically in cancer; they have had an important role in addressing patients’ and families’ necessities. Although they occupy a central role, there is no clarity about who they are, how they are organised, the goals that guide their performance and how they materialize social participation in health. Based on that, this study aimed to explore the characteristics of civil society organisations that work in cancer in Chile and to identify the networks they build with other actors to achieve their goals. Materials and methods Qualitative case study using semi-structured online interviews with organisation representatives, politicians, decision-makers and academics related to cancer in Chile. Content analysis was performed, admitting emerging categories from the participants’ narratives. Results Three main profiles of organisations were identified: (i) Long-established organisations focused on influencing public policy and decision-making in cancer, (ii) Growing organisations focused on informing and supporting families and patients, (iii) Newly established organisations focused on patient well-being, such as sports activities. Relationships between groups and other actors involve perceived benefits like the growth of the organisations and funding for activities. However, perceived barriers and inequities are also identified, mainly lack of financial resources, competition between organisations and insufficient information. Discussion The objectives of civil society organisations in cancer are diverse and reflect multiple ways of practising social participation in health. Tensions generate unequal participation and missed opportunities to promote public health in cancer in Chile. The study highlights the importance of recognising cancer social organisations as essential actors in public health. It is crucial to involve them in formulating and implementing comprehensive responses to maximise the opportunities for progress in this field.